STUDENTS’ STRATEGIES IN RESPONDING TEACHERS’ ORAL QUESTIONS - Foristia Kencana Wensi; Hilda Puspita; Rudi Afriazi (Universitas Bengkulu, 2018)
The aim of this research was to find out the strategies used by the English Education Study Program students in responding teacher oral questions. The research was designed as a descriptive quantitative research. The population of the research was sixth semester students of English Education Study Program of Universitas Bengkulu in the 2017/2018 academic year. The samples were 69 students. The data were collected by using a set of questionnaire. There were 25 statements of responses strategies which consisted of seven categories of response strategies proposed by Lui et. al (2018) and any communication strategies proposed by Dornyei (1997). They were avoidance strategy, accommodative strategy, asking for clarification strategy, no response strategy, excuse strategy, denial strategy and apology strategy. The result of this study showed that students of English Education Study Program preferred to use six categories i.e., accommodative strategy, asking for clarification strategy, no response strategy, excuse strategy, and denial strategy and one was seldom used namely apology strategy. In addition, the most frequently used strategy group by the students was avoidance strategy.